A SCYL2 gene from Oryza sativa is involved in phytosterol accumulation and regulates plant growth and salt stress - Xu, Minyan (Plant science : an international journal of experimental plant biology, 2024)
Copyright © 2024 Elsevier B.V. All rights reserved.